Perlindungan Karya Batik Tradisional Kampung Pesilat Melalui Merek Kolektif - Ria Setyawati; Mas Rahmah; Normandyarsa Rahman (Pelita Masyarakat, 2023)
Traditional batik products made by artisans in a community or region are often not aware of the importance of protecting their work through Intellectual Property Rights, especially brands. Even though the potential for the development of traditional batik products can be optimized through brand protection. An example is the traditional batik work produced by the people of Kampung Pesilat in Madiun Regency. Kampung Pesilat's batik creations already exist and have been passed down from generation to generation until now, the batik craftsmen still carry out small-scale production. This research will examine the proper brand protection for the development of traditional Batik handicraft products. This research is legal research, namely normative legal research. The approach used is the statute approach and conceptual approach.